The Effectiveness of Kant's Conscientious Moral Conservative Role and Moral Strategies in Reducing Organizational Violations through the Mediating Role of Job Motivation - liela nemati; siroos ghanbari; Rasool Rostami Mal Khalifa; soheil sarshar (Allameh Tabataba'i University Press, 2019)
The method is descriptive-correlation of structural equations in terms of practical purpose and in terms of data collection method. The statistical population includes all education staff in Hamadan. The sample size was randomly selected based on the relative class method (between the two classes of education one and two) and based on Kerjcie and Morgan table 210. Research tools include researcher-made questionnaires of Kant's ethical conscientious view, organizational violations and standard questionnaires of ethical strategies of Nemati et al. (2020) and Hackman and Oldham (1980) job motivation. The validity of the questionnaire was confirmed by three management experts. The reliability of the tools through Cronbach's alpha test for Kant's ethical conscientious view was 0.89, ethical strategies 0.84, job motivation 0.90 and administrative violations 0.82, respectively. Two levels of descriptive statistics (percentage, frequency, mean and standard deviation) and inferential statistics (Pearson correlation coefficient test of structural equation type) were used to analyze the research data. The results showed that Kant's conscientious view has a direct effect on job motivation and reduction of organizational violations. Ethical strategy also has a direct effect on job motivation and reduction of organizational violations. Job motivation has an effect on the reduction of organizational violations. Thus, Kant's ethical conscientious view and ethical strategies are effective in reducing organizational violations by mediating the role of job motivation.